Extracellular protease activities of extremely halophilic archaea and their control via direct electric current - (:unkn) unknown (SOC LEATHER TECHNOL CHEMISTS, 2008)
Proteolytic enzymes which are produced by extremely halophilic Archaea present in salt may cause serious 14 damage on salted hides and may result in significant economic losses in the leather industry. Hence, protease activities of 24 protease producing extremely halophilic archaeal strains isolated from Tuz Lake, Kaldirim and Kayacik salterns and Tuzkoy salt mine were determined in this study. The protease activities of Tuz Lake, Kaldirim and Kayacik saltern and Tuzkoy salt mine strains were found as between 80.0 and 83.3, 81.1 and 83.8, 83.3 and 83.4, 82.0 and 83.4 Units, respectively. To prevent proteolytic haloarchaeal damage on brine cured hides, the protease producing strains were treated with 0.5A direct electric current for 20min. Although proteolytic strains of Tuz Lake and Tuzkoy salt mine in the liquid gelatin media were killed by 0.5A direct electric current within 15min, 10min direct electric current treatment were enough to kill all proteolytic strains of Kaldirim and Kayacik salterns. Also, the effect of 0.5A direct electric current on protease activities of the test strains was examined during 20min treatment in this study. It was found that 0.5A direct electric current caused a slight decrease on protease activities of the test strains. Therefore, it is necessary to kill protease producing strains in brine solution with direct electric current before the excretion of their protease into the brine solution.
Keywords: SERINE PROTEINASE; BACTERIA; INACTIVATION; PURIFICATION; MEDITERRANEI; METABOLISM; SEAWATER; QUALITY; WATER; MILK